2019
DOI: 10.3390/molecules24234277
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Tea (Camellia sinensis) and Its Active Constituents in Cosmetics

Abstract: Studies on the cosmetic applications of plant extracts are increasingly appearing in the scientific literature, which is due to the growing popularity of skincare products around the world. In the light of the observed changes, a return to natural treatment and skincare with cosmetics free of harmful substances or toxic preservatives is visible. Currently, tea extracts, due to their rich composition and various biological actions, play an important role among the dietary supplements and cosmetics. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 100 publications
(122 reference statements)
0
45
0
7
Order By: Relevance
“…Oxidative stress is one of factors inducing skin aging processes and inhibiting its regeneration ability [ 7 ]. Long-term oxidative stress in skin cells (occurring e.g., after prolonged skin exposure to the sun, as well as due to many external factors, e.g., smog) may leads to DNA, protein and lipid damage, disrupting many natural processes, including degradation and synthesis of collagen and elastin-basic proteins that play the most important role in a skin aging process, regeneration or wound healing [ 24 , 25 , 26 ]. Chlorophyll may also enhance the antioxidant effect [ 6 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is one of factors inducing skin aging processes and inhibiting its regeneration ability [ 7 ]. Long-term oxidative stress in skin cells (occurring e.g., after prolonged skin exposure to the sun, as well as due to many external factors, e.g., smog) may leads to DNA, protein and lipid damage, disrupting many natural processes, including degradation and synthesis of collagen and elastin-basic proteins that play the most important role in a skin aging process, regeneration or wound healing [ 24 , 25 , 26 ]. Chlorophyll may also enhance the antioxidant effect [ 6 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in previous studies [ 27 , 28 , 29 , 30 , 31 , 32 ], the total content of phenols per 1 g of dried plant or dry extract is about 0.09–0.56 mg in hemp leaves, 4.7–8.1 mg in flowers, 0.77–51.6 mg in seeds and 10.51–52.58 mg in inflorescences. In the research of Maqsood et al [ 26 ] the influence of different solvents on the concentration of antioxidants in cannabis leaf extracts was compared. It was shown that the highest content of phenols was characterized in aqueous and methanolic extracts, while extracts obtained using organic solvents did not show the content of phenols.…”
Section: Resultsmentioning
confidence: 99%
“…Catechins are considered the prominent flavonoids in GT which gained attention for their use in various diseases due to their antiaging, anticancer (Beltz et al, 2008), antiparkinsonism, antistroke, antidiarrheal, antidiabetic (Subramani & Natesh, 2003), anticaries and antibacterial (Hamilton‐Miller, 2001), antifibrotic, anti‐inflammatory, antioxidative (Singh et al., 2011), and antiatherosclerotic activities (Hussain et al., 2017). Catechin derivatives (flavonoids), including epicatechin, epigallocatechin, epicatechin gallate, and epigallocatechin gallate, showed the most potent anti‐inflammatory and anticancer activities (Koch et al., 2019). Owing to the various health‐promoting properties of catechins, it is recommended that products containing catechins be included in the daily diet (Musial et al., 2020; Singh et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…C. sinensis of the Theaceae family is locally termed as ‘cha’ in Bangladesh and as ‘black tea’ worldwide [ 146 ]. The leaves, stems, and twigs contain different active constituents like flavonoids (e.g., thearubigins, theaflavins, and catechins), vitamins amino acids, β-carotene, chlorogenic acids, volatile compounds carbohydrates, phenolic acids (e.g., gallic acid, caffeic acid, and cauramic acid), proteins, lipids, and fluoride [ 147 , 148 ]. These components help in the treatment of different diseases with their different protective properties [ 146 ].…”
Section: Plant Mediated Treatment Of Ulcer and Inflammatory Diseasesmentioning
confidence: 99%